Biliary atresia - Miurkis Endis Miranda; Ramón Villamil Martínez; Pastor Thomas Olivares (Medisur)
Biliary atresia is an obstructive and progressive process of unknown etiology that affects intra and/or extrahepatics biliary tracts and cause neonatal jaundice by serious obstruction of the biliary flow. It is presented with a frequency of 1 by each 10 000 – 15000 born alive. Is not hereditary and the most probable etiology is the progressive inflammatory illness of the biliary tracts. We presented the Good Clinical Practices Guideline for Biliary atresia, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba, March, 2005).